Infectious keratitis secondary to Histoplasma capsulatum: the first case reports in humans - Enyr S. Arcieri; Ademir Rocha; Camila N. Mendonça; Eduardo G. V. Andreo; Ioná G.A. Finotti; Rafael L. Furlanetto; Rafael S. Arcieri; Flávio J. Rocha; Luiz V. Rizzo (Brazilian Journal of Infectious Diseases)
The authors report an unusual case of fungal keratitis caused by Histoplasma capsulatum in a male immunocompetent patient. PCR confirmed the presence of the fungus DNA in the material studied. To our knowledge this is the first reported case in humans described all over the world.